VacZineNations!, a Critical Dialogue - Knowles, Rachelle Viader; Tonoyan, Mkrtich; Mahon, Patrick; Hammersley, John; Webb, Lisa (Imaginations)

(untitled) (York University, 2020)
VacZineNations! is a collaborative artwork led by Rachelle Viader Knowles and Mkrtich Tonoyan, produced by artists, students, and designers in the UK, Canada, China, and Armenia, and exhibited as part of at Galleri KiT in Trondheim, Norway, and UNAIDS in Geneva, Switzerland, in 2017. This critical dialogue text gives insight into the necessarily messy approach used to develop a project with over one hundred participants, working from multiple disciplinary and geographic perspectives. This text is accompanied by a second essay that positions the artwork within the context of practice-led research (see Knowles, “VacZineNations! as Practice-Led Research” in this volume).